The festival of March the third - Li, Song (Chinese Festival Culture Series., 2014)
'The Festival of March the Third' is the day of sacrifice to ancestors, gods, and saints in China. This book introduces the origin, development, dissemination, activities, and distinctive local features of this Chinese festival. Different from 'The Tomb-Sweeping Day, ' 'The Festival of March the Third' has religious implications for worshipping Buddhism and Taoism, warding off evil spirits, and purifying the mind. The book - written in an English-Chinese bilingual text - not only introduces the history and development of the festival, but also presents many touching folk tales and heroic legend.